2004
DOI: 10.1007/s00198-004-1791-2
|View full text |Cite
|
Sign up to set email alerts
|

Balance disorder and increased risk of falls in osteoporosis and kyphosis: significance of kyphotic posture and muscle strength

Abstract: This controlled trial was designed to investigate the influence of osteoporosis-related kyphosis (O-K) on falls. Twelve community-dwelling women with O-K (Cobb angle, 50-65 degrees measured from spine radiographs) and 13 healthy women serving as controls were enrolled. Mean age of the O-K group was 76 years (+/-5.1), height 158 cm (+/-5), and weight 61 kg (+/-7.9), and mean age of the control group was 71 years (+/-4.6), height 161 cm (+/-3.8), and weight 66 kg (+/-11.7). Quantitative isometric strength data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
247
2
23

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(279 citation statements)
references
References 37 publications
7
247
2
23
Order By: Relevance
“…We have previously published that the correlations between these four different measures were strong, ranging between 0.63 and 0.76, and our current study findings provide solid evidence of construct validity [24]. In related literature, several reports of varying quality have been published that employed alternative measures for kyphosis and used balance as a surrogate outcome for falls [19,20,[28][29][30][31][32][33]. These studies as a whole suggest that kyphosis adversely affects balance, and it is known that poor balance is a fall risk factor.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We have previously published that the correlations between these four different measures were strong, ranging between 0.63 and 0.76, and our current study findings provide solid evidence of construct validity [24]. In related literature, several reports of varying quality have been published that employed alternative measures for kyphosis and used balance as a surrogate outcome for falls [19,20,[28][29][30][31][32][33]. These studies as a whole suggest that kyphosis adversely affects balance, and it is known that poor balance is a fall risk factor.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, a study of women with chronic back pain found OWD was associated with balance and gait issues, both of which could lead to increased fall risk [29]. Using the Debrunner Kyphometer as a measure of kyphosis, a large study of women found that greater quartiles of kyphotic angle were associated with longer TUG times in fully adjusted models [32], while a small study of women found that hyperkyphotic women had reduced gait velocity and reduced falls efficacy compared to women with normal kyphosis [33]. However, in contrast, two other published studies reported no association between kyphosis and the Berg Balance Score [20] and force plate measures of balance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, number of underlying diseases, motor paralysis, impaired vision, decreased muscle strength, body imbalance, and history of falling have been reported as risk factors for fall [9,34]. A study of 12 female osteoporosis patients with thoracic kyphosis showed poor balance and an increased propensity to fall on a fall efficacy scale [37]. But, unfortunately, detailed data on spinal sagittal alignment and ROM were not included, and the history of fall was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic kyphosis, assessed using Cobb's angle, has been proved to be associated with poor physical fitness, osteoporosis, and the risk of falls (12,13). However, measuring Cobb's angle requires radiologic equipment and therefore this measure is not easily performed.…”
Section: Discussionmentioning
confidence: 99%